A peridynamic formulation for nonlocal bone remodelling - Schaller, Emely; Javili, A.; Schmidt, Ina; Papastavrou, Areti; Steinmann, Paul (Computer Methods in Biomechanics and Biomedical Engineering, 2022)
Bone remodelling is a complex biomechanical process, which has been studied widely based on the restrictions of local continuum theory. To provide a nonlocal bone remodelling framework, we propose, for the first time, a peridynamic formulation on the macroscale. We illustrate our implementation with a common benchmark test as well as two load cases of the proximal femur. On the one hand, results of our peridynamic model with diminishing nonlocality measure converge to the results of a local finite element model. On the other hand, increasing the neighbourhood size shows to what extent the additional degree of freedom, the nonlocality, can influence the density evolution.
CRIS-Team WoS Importer:2022-04-29
Keywords: Bone remodelling; peridynamics; nonlocal material; density evolution; influence of nonlocality